¿Dondé está el agua? - Wendy J. Dahl (EDIS)
Foods vary widely in water content. You may be surprised to find out that many common foods that are not liquids are quite high in water! This 5-page Spanish-language fact sheet offers a brief quiz and pictorial answer key, written by Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, May 2011.